An Assessment of Empirical Thinking in Islam: Penilaian Terhadap Pemikiran Empiris dalam Islam - Kusuma, Kumara Adji (Indonesian Journal of Islamic Studies, 2024)
This research explores the intersection between empiricism and Islamic epistemology, focusing on the limitations of sensory perception in capturing reality. Although empiricism plays an important role in Islamic thought, its exclusive reliance on sensory experience limits the understanding of phenomena beyond perception. Through a comparative analysis of Islamic philosophical texts and empirical literature, this study reveals the compatibility of empirical inquiry with metaphysical insights in Islam. By advocating a holistic approach to acquiring knowledge, this research contributes to the broader philosophical discourse, emphasizing the synthesis of empirical methods with spiritual insights for a comprehensive understanding of reality. Highlights : Empirical limitations: Highlighting the constraints of sensory perception in grasping reality. Compatibility of methodologies: Demonstrating the harmony between empirical inquiry and Islamic metaphysical principles. Synthesis of knowledge: Advocating for a holistic approach that integrates empirical methods and spiritual insights for a comprehensive understanding of reality. Keywords: Empiricism, Islamic epistemology, Sensory perception, Metaphysical insights, Holistic approach